P5 Introducing Bronchial Thermoplasty Treatment into a Severe Asthma Clinical Service. (19th November 2012) - Bicknell, S; Chaudhuri, R; Shepherd, M; Lee, N; Pitman, N; Spears, M; Cameron, E; Cowan, D; Nixon, J; Thompson, J; Thomson, NC
Abstract : Introduction and Objectives: Bronchial thermoplasty involves the delivery of radio frequency energy to the airways during flexible bronchoscopy, and possibly exerts its effect by reduction of airway smooth muscle mass (1). Clinical trials of bronchial thermoplasty have shown benefits in the treatment of patients with moderate or severe asthma. We describe our experience of introducing bronchial thermoplasty into a severe asthma clinical service. Methods: Funding was obtained from the Greater Glasgow and Clyde NHS Health Board to evaluate bronchial thermoplasty in the treatment of ten patients with moderate to severe asthma. Patients were assessed at the Difficult Asthma Clinic and selected for the procedure using criteria similar to those employed in clinical trials of bronchial thermoplasty. Patients on all forms of asthma medication were eligible for treatment including omalizumab and oral prednisolone. Procedures were performed by 2 physicians or by 1 physician and a nurse, using conscious sedation with alfentanyl and midazolam. One patient required deeper sedation [remifentanyl and propofol] due to a complicated medical history. Bronchial thermoplasty was administered in three sessions, treating the right lower lobe, the left lower lobe and both upper lobes respectively. Follow up is at 3 monthly intervals for both safety and efficacy outcomes. Results: Between 2nd June 2011 and 30th April 2012, ten patients underwent bronchial thermoplasty in Glasgow [7 males, 3 females] (Table 1 ). Six patients were at Step 5 and four at Step 4 of the British Guideline on the Management of Asthma scale. 4/10 were taking oral prednisolone daily and 2/10 were receiving omalizumab treatment [for 4th year and 3rd year respectively]. Treatment sessions were largely uneventful and adverse effects were similar to those reported in clinical trials. To date, there has been a reduction in some asthma medications: two patients receiving omalizumab have successfully discontinued treatment; those taking oral steroids are being weaned off prednisolone. Conclusion: Bronchial thermoplasty can be safely delivered in a clinical setting to patients with severe asthma. References: Thomson NC, Bicknell S, Chaudhuri R Bronchial thermoplasty for severe asthma. Curr Opin Allergy Clin Immunol 2012; 12:241–248.